Capacidade antioxidante e compostos bioativos em hortaliças analisadas em dois períodos de cultivo - Marcussi, Flávia [UNESP] (2015)
Regular consumption of fruits, vegetables and grains rich in antioxidants, such as phenolic compounds, vitamin C and carotenoids, has been associated with many benefits to human health. His presence in the diet can help in protecting the body against oxidative stress, avoiding and preventing so, a number of chronic degenerative disorders. In plants there can be variations in the content of bioactive compounds, depending on the genetic variety, growing conditions, climate, maturity stage and postharvest factors. The objective of this study was to evaluate three lettuce cultivars (Lactuca sativa L.), which were the lettuce american, curly and smooth, and also three varieties of condiments, coriander (Coriandrum sativum L.), parsley (Petroselinum crispum (Mill.) Nym.) and spring onion (Allium fistulosum L.) cultivation in two periods on the content of phenolic compounds (TPC), total antioxidant capacity (TAC), phenolic acids and flavonoids, chlorophyll and carotenoids. Three lots of each sample were acquired in the local market of Araraquara-SP in two cultivation periods: August 2013 [1º period]; and January/February 2014 [2º period] and its leaves (edible parts) were dried for determination. Analyses were performed individually in triplicate and the results expressed as mean ± standard deviation. Coriander, Smooth lettuce and Curly lettuce showed high levels of and TAC. Few vegetables showed differences between the cultivation period in the analyzes, especially coriander. The total chlorophyll content of condiments was higher in the samples analyzed in the 2º period. Among the three varieties of lettuce, the curly lettuce showed the highest TPC and TAC levels while the cabbage lettuce had the lowest. It follows that it is of great importance to know the different bioactive compounds present in the vegetables and the variation of their content in the analyzed cultivation ...